Modeling of efficient key management method in multicast networks. - Mehdizadeh, Abbas; Hashim, Fazirulhisyam
This paper proposes a cost-effective key management method for multicast networks. This method divides a multicast group into several subgroups, where the multicast transmission is separated into two levels, namely, multicast and unicast level. We model our proposed method based on the cost of join and leave operations in the multicast group using Markov chain and Poisson Arrival Process. Then, we compare its performance (by means of analytical) against typical key treebased methods. The results show that our proposed method significantly reduces key update cost compared to the existing ones.